Effect of Precooking and Superheated Steam Treatment on Quality of Black Glutinous Rice - Chinnatat Piyawanitpong; Nantawan Therdthai; Wannasawat Ratphitagsanti (Journal of Food Quality)
Consumption of glutinous rice has been increasing. Leum Pua rice (Oryza sativa Linn.) is black glutinous rice containing high nutrition, but its cooking process is time-consuming. This study aimed at decreasing cooking time by changing rice properties using superheated steam treatment. The black glutinous rice was subjected to pretreatment: uncooking and precooking before superheated steam treatment at 250°C and 300°C. Drying rate constant (k) of uncooked rice was 0.0301–0.0744 s−1. Precooking rice prior to superheated steam treatment at 300°C reduced the kinetic rate constant to 0.0596 s−1. From SEM, porosity of the treated rice was observed. However, superheated steam treatment reduced ferric reducing antioxidant power and total phenolic content, compared with control. From X-ray diffraction, A-type crystalline structure of the treated rice was disappeared. Cooking time of the superheated steam-treated rice was reduced to 1–5 min. Their hardness and overall liking scores were comparable to control.